Borrowing and Returning Oxygen Atom in Trifluoroacetic Anhydride Transfer to Nitrones: A Versatile Route for the Synthesis of N‐Trifluoroacetyl Amides. Issue 6 (28th December 2018) - Wang, Junwen; Weng, Zhiqiang
Abstract : A method for the synthesis of N ‐trifluoroacetyl amides through trifluoroacetic anhydride transfer to nitrones by borrowing and returning oxygen atom is reported. The reaction appears to proceed via electrophilic trifluoroacetylation, followed by nucleophilic addition and elimination, and intramolecular substitution, affording N ‐trifluoroacetyl amides in good to excellent yields. The present method tolerates a wide range of functional groups. Also, nitrones react with difluoroacetic anhydride providing the corresponding N ‐difluoroacetyl amides. Moreover, the method described could be of interest from a biological point of view, because it constitutes a straightforward strategy for the synthesis of biologically active N ‐trifluoroacetyl amide analogues. Abstract : A variety of N ‐trifluoroacetyl amides are obtained from trifluoroacetic anhydride transfers to nitrones through borrowing and returning oxygen atom. This transformation proceeds smoothly under mild conditions via electrophilic trifluoroacetylation, followed by nucleophilic addition and elimination, and intramolecular substitution. Furthermore, the method also provides efficient access to N ‐difluoroacetyl amides. This work presents a straightforward access to the valuable N ‐fluoroacetyl amides from readily available and inexpensive starting materials.